Genome-Wide Identification and Analysis of the MADS-Box Gene Family in Theobroma cacao - Qianqian Zhang (MDPI AG, 2021)
The MADS-box family gene is a class of transcription factors that have been extensively studied and involved in several plant growth and development processes, especially in floral organ specificity, flowering time and initiation and fruit development. In this study, we identified 69 candidate MADS-box genes and clustered these genes into five subgroups (Mα: 11; Mβ: 2; Mγ: 14; Mδ: 9; MIKC: 32) based on their phylogenetical relationships with Arabidopsis. Most TcMADS genes within the same subgroup showed a similar gene structure and highly conserved motifs. Chromosomal distribution analysis revealed that all the TcMADS genes were evenly distributed in 10 chromosomes. Additionally, the cis-acting elements of promoter, physicochemical properties and subcellular localization were also analyzed. This study provides a comprehensive analysis of MADS-box genes in Theobroma cacao and lays the foundation for further functional research.